The information impact of network media, the psychological reaction to the COVID-19 pandemic, and online knowledge acquisition: Evidence from Chinese college students - Xuefang Xie; Zhipeng Zang; José M. Ponzoa (Journal of Innovation & Knowledge (JIK), 2020)
This study focuses on whether network media information about the COVID-19 pandemic has had a significant impact on the online knowledge acquisition of college students. This research is of great significance, as it can have a profound impact on the way we think about knowledge acquisition in the future. Yet, a recent literature review finds that the academic community has not paid attention to this important topic. In the present work, which is based on a survey of 5000 Chinese college students during the COVID-19 pandemic period, we find that COVID-19 information from mainstream Chinese media and overseas media as well as social media has had a significant promoting effect on the online knowledge acquisition of college students. At the same time, the psychological response to the pandemic situation is shown to have had a significant mediating effect on the relationship between the information impact from mainstream Chinese and overseas media and the online knowledge acquisition of college students. Our findings have shown that the more positive college students are in responding to the pandemic, the stronger their willingness is to acquire knowledge through online means, and the better effect this will have on them acquiring knowledge. The results of this paper have important implications for the optimization and improvement of college students' education and knowledge acquisition methods in the context of the long-term COVID-19 pandemic.
Keywords: 650; COVID-19 pandemic; Information impact; Network media; Online knowledge acquisition; Psychological reaction; Coronavirus; Studierende; Informationsverhalten; Mediennutzung; China